Politically incorrect literature? A feminist critique of the sexual discourse of the modern Malay novel - Washima Che Dan, (Universiti Kebangsaan Malaysia, 2006)
This article frames its discussion within the sociolinguistic sphere of prescriptive versus descriptive debates on language, juxtaposing the verbal hygiene practice of political correctness with definitions of what is literature. The language under scrutiny here is the language of the modern Malay novel, particularly pertaining to its treatment of sex and sexuality. A feminist critique of the language of the modern Malay novel in relation to verbal hygiene practices reveals a predictable disregard of political correctness in the way that women and their sex and sexuality are represented. It is proposed that a feminist reading of the modern Malay novel can contribute to the discussion of what is literature within Malay Muslim contexts